An experimental study on mechanical properties and wear of A380/nB4C composites fabricated using two different liquid state processes - Singh, Jaivir; Alba-Baena, Noé; sharma, vishal; Trehan, Rajeev (2021)
In the present work, fabrication of metal matrix composite of aluminium alloy A380 reinforced with 0.5, 1 and 1.5 weight percentages of nano boron carbide through mechanical stirring and ultrasonic treatment processes. Scanning Electron Microscopy (SEM), Back Scattered Electron Detector (BSE) and energy-dispersive X-ray spectroscopy (EDS) are used to characterize fabricated composites. Furthermore, tensile, hardness, and wear tests are performed to compare the mechanical and wear properties of prepared samples. It is found that UST is an efficient process as compared to MS for refining the microstructure of base alloy and fabricated composites. Also, the reinforced particles are efficiently and uniformly distributed in the ultrasonic treatment process. The improved properties of the ultimate tensile strength (UTS) and hardness observed at A380/1nB4C as 57%, and 35% respectively and wear of the fabricated composites samples is less as compared to the base alloy.